STRUKTUR KOMUNITAS SERANGGA TANAH PADA EKOSISTEM PERTANIAN DAERAH ALIRAN SUNGAI (DAS) BRANTAS HULU DESA SUMBEREJO KECAMATAN BATU KOTA BATU - Imam Fauzi Rohman; Abdulkadir Rahardjanto; Moch Agus Krisno B (Universitas Sebelas Maret, 2014)
Soil insects are insects that live in thesurface of soil and living in the soil. The current of soil insects population on agricultural ecosystems very rare as a result of intensive farming and modern farming practices using synthetic chemical fertilizers and synthetic insecticides. Another problem is the lack information of soil insects contained in agricultural ecosystems Brantas Watershed Sumberejo Batu.The research aims to determine of the spesies, parameters of ecology, species diversity index, and evenness index contained in agricultural ecosystems Brantas Watershed Sumberejo Batu. This research used descriptive quantitative research. This research carried out in the morning with the plot method(squares) and using Pitfalls Trap. Datawere collected by direct observation of the population investigated. The results showed that soil insects were found to consist of a species Pheidole capellinii, Iridomyrmex sp, Pachycondyla sp, Camponotus sp, Monomorium sp, Pheropsophus occipital, Gabrius sp, dan Teleogryllus siamensis. Soil insect of ecology parametersare: (1) density ranged from 4,15 ind/m2 – 27,26 ind/m2, relative density between 0,01-0,09, The highest density of species is Pheidole capellinii, and lowest is Monomorium sp. (2) frequency ranged between 0,15-0,63, the relative frequency ranged from 0,04-0,16 with the highest frequency value of species is Pheidole capellinii 0,94, and lowest is Monomorium sp. 0,06. (3) the highest Importance Index Valueof species is Pheidole capellinii 0,25, the lowest is Monomorium sp. 0,06. Index of diversity values Shannon wiener (H') of 0,73 or categories is very low diversity values. Index of Evenness(E) is 0,33 which means that the population tends to be unevenor low(E <0.4). Keywords: soil insects, agriculturalecosystems, community structure.